MAGNETIC DRUG DELIVERY AND TARGETING: PRINCIPLES AND APPLICATIONS - Babincova, Melania; Babinec, Peter (Biomedical papers, 2009)
Background: Nanomaterials are at the leading edge of the rapidly developing field of nanotechnology. Magnetic nanoparticles for cancer therapy and diagnosis have been developed on the basis of their unique physico-chemical properties not present in other materials. Their versatility is widely exploited in such diverse techniques as cell and macromolecule separation and purification, immunoassays, targeted drug delivery, controlled material release, electromagnetic hyperthermia, gene therapy, or magnetic resonance imaging. In this review we concentrate on the physical principles of magnetic drug targeting and biomedical applications of this technique.Methods and results: We examined several databases, PubMed, ISI Web of Knowledge, and Scopus, for the period 1985-2009, with specific attention to studies that used targeting of magnetic nanoparticles especially in the therapy and diagnostics of tumors. We have also presented several of our own results on theoretical simulations of magnetic particle motion in external magnetic field.Conclusions: We found growing number of published papers in this field of nanomedicine, showing the almost unlimited potential of magnetic nanoparticles in the field of experimental and clinical oncology.
Keywords: Magnetic nanoparticles/Cancer therapy/Drug targeting/Gene Therapy/Controlled drug release